Synergistic effects of psyllium husk powder and different levels of methylcellulose on the storage stability of sodium caseinate emulsion - Fu, Qing-quan; Zhou, Lei; Shi, Hai-bo; Wang, Rong-rong; Yang, Lin-wei (Frontiers in Nutrition, 2023)
The study investigated the effects of compound fibers composed of psyllium husk powder (PHP, 0.3%) and methylcellulose (MC, 0, 0.3%, 0.6%, 0.9%, and 1.2%) on the storage stability, rheology, and microstructure of sodium caseinate emulsions. Results showed that the emulsion stability was enhanced with the increased concentrations of MC, especially at the concentration of 1.2%. The oil droplet size in the emulsions was decreased as the concentrations of compound fibers was increased, which was further confirmed by the optical microscope analysis. The rheological measurements and cryo-scanning electron microscopy results indicated that compound fibers improved the viscosity of the emulsions, and formed a strong three-dimensional network structure. The results of confocal laser scanning microscope and surface protein concentration measurements showed that compound fibers were evenly distributed into the oil droplet surface. The above results demonstrate that compound fibers are an effective thickener and emulsifier in enhancing the stability properties of O/W emulsions stabilized by sodium caseinate.